Adsorption Behaviour and Kinetics of Zearalenone on Hydroxyl-Fe-Al-Intercalated Montmorillonite - Shengqiong Fang; Yueqi Xiao; Huiqiang Wang (Journal of Nanotechnology)
Pristine montmorillonite (Mont) was used as raw materials to prepare hydroxyl-Fe-pillared Mont, hydroxyl-Al-pillared Mont, and hydroxyl-Fe-Al-pillared Mont composites. By varying the OH/Fe and Fe/Al molar ratios during the preparation of the pillared Mont, the adsorption capacity of zearalenone (ZEA) and the kinetics were elucidated. The characterization of X-ray diffraction (XRD) and Fourier transform infrared (FT-IR) spectroscopy reveals the adsorption mechanism of pristine and modified Mont. The results indicated that the ZEA adsorption capacity is Mont (0.05 mg/g) << 1.5OH/Fe-Mont (0.28 mg/g) << OH/Al-Mont (0.51 mg/g) < 0.5Fe/Al-Mont (0.56 mg/g) in the condition of pH = 8 and 37°C, in which both 0.5Fe/Al-Mont and OH/Al-Mont reached maximum adsorption capacity and 1.5OH/Fe-Mont attained 5 times the capacity of Mont. Adsorption isotherm studies revealed that Freundlich adsorption isotherms best represented the experimental data. The kinetic data for ZEA adsorption revealed that the Mont adsorption capacity for ZEA equilibrates in 1 hour and is best described using the pseudo-second-order rate equation. The XRD analysis indicated that the amplification of Fe-dominant pillared Mont interlayer spacing is the main reason for the observed increases in the adsorption capacity of ZEA, while Al-dominant pillared Mont has a relatively stable Keggin structure; therefore, interlayer spacing is not the primary mechanism for changes in the adsorption capacity of both OH/Al-Mont and Al-dominant pillared Mont. An FT-IR analysis demonstrated that cationic exchange was the dominant mechanism that allowed ZEA and hydroxyl-Al ions to enter the Mont interlayers, while this cationic exchange mechanism was not the dominant mechanism used by hydroxyl-Fe entering the Mont layers.